2018
DOI: 10.1002/bip.23224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ferric citrate on amyloid‐beta peptides behavior

Abstract: Amyloid beta (Aβ) aggregation and oxidative stress are two of the central events in Alzheimer's Disease (AD). Both these phenomena can be caused by the interaction of Aβ with metal ions. In the last years the interaction between Zn , Cu , and Aβ was much studied, but between iron and Aβ it is still little known. In this work we determine how three Aβ peptides, present in AD, interact with Fe -citrate. The three Aβ peptides are: full length Aβ1-42, an isoform truncated at Glutamic acid in position three, Aβ3-42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…In vitro studies have also found that iron can promote aggregation of Aβ peptides and increase their cytotoxicity ( Tahmasebinia and Emadi, 2017 ; Galante et al, 2018 ). However, there are different opinions on the role of iron and Aβ.…”
Section: Brain Iron Dyshomeostasis and The Pathophysiology Of Alzheimmentioning
confidence: 99%
“…In vitro studies have also found that iron can promote aggregation of Aβ peptides and increase their cytotoxicity ( Tahmasebinia and Emadi, 2017 ; Galante et al, 2018 ). However, there are different opinions on the role of iron and Aβ.…”
Section: Brain Iron Dyshomeostasis and The Pathophysiology Of Alzheimmentioning
confidence: 99%
“…In vitro work has also suggested a causative role for iron in the formation of β-amyloid aggregates—treatment of neurons with ferric citrate facilitated non-amyloidogenic processing of APP ( Chen et al, 2018 ). Similarly, treatment of β-amyloid peptides with ferric citrate promotes aggregation ( Galante et al, 2018 ) and iron chelation decreases it ( Tahmasebinia and Emadi, 2017 ). In vivo , increasing the brain iron of APP mice through dietary overload has been shown to potentiate iron accumulation in amyloid plaques and microgliosis ( Peters et al, 2016 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Interestingly however, in a recent study ferric iron treatment in rat cortical neurons facilitates non-amyloidogenic processing of APP via α-secretase, intracellular localization of sAPPα impaired enzymatic activity of β-secretase, and thus decreases levels of sAPPβ and Aβ (Chen et al, 2018). Boopathi and Kolandaivel (2016) show that ferrous iron induces a structural conformation in Aβ toward a β-sheet structure which tends to form oligomers and fibrils, whereas other groups demonstrate that ferric iron promotes aggregation of both Aβ 40 and Aβ 42 as well as cytotoxicity in vitro (Tahmasebinia and Emadi, 2017; Galante et al, 2018). Aβ 42 promotes magnetite nanoparticle formation (Tahirbegi et al, 2016), thus coming full circle and providing evidence for a causative role of iron in AD pathogenesis.…”
Section: Iron In Neurodegenerative Diseases – a One-size-fits-all?mentioning
confidence: 99%